Preposition of Customary Language on Manjapuik Marapulai of Pasambahan Text in Solok City, West Sumatera - Eriza Nelfi; Elvina A. Saibi; Iman Laili (Ranah: Jurnal Kajian Bahasa, 2023)
This study aims to describe the preposition of the various convention languages in the text of Pasambahan Manjapuik Marapulai (hereinafter abbreviated as TPMM) in Solok City, West Sumatera. TPMM is one of a series of marriage ceremonies carried out according to Minangkabau custom in Solok City. The method in this study uses a qualitative descriptive method with the object of study in the form of prepositions in TPMM. The research data is in the form of sentences containing prepositional phrases contained in the TPMM. For data collection, the listening method was used with note-taking techniques. Furthermore, to analyze the data, the distribution method was used with the direct element division technique as a basic technique and an advanced technique in the form of marking reading techniques. The results of the research show that the prepositional forms found are the basic prepositions and the derived forms in the form of combined prepositions of type the meaning found is the place of being, the place of origin, the place of destination, origin, a certain place, comparison, and inclusion.  AbstrakPenelitian ini bertujuan untuk mendeskripsikan preposisi bahasa ragam adat dalam teks Pasambahan Manjapuik Marapulai (selanjutnya disingkat dengan TPMM) di Kota Solok, Sumatera Barat. TPMM adalah salah satu rangkaian upacara proses perkawinan yang dilakukan secara adat Minangkabau di Kota Solok. Metode dalam penelitian ini menggunakan metode deskriptif kualitatif dengan objek kajian  berupa preposisi dalam TPMM. Data penelitian ini berupa kalimat yang mengandung frasa preposisional yang terdapat dalam TPMM. Untuk pengumpulan data digunakan metode simak dengan teknik catat. Selanjutnya, untuk menganalisis data digunakan metode agih dengan teknik  bagi unsur langsung sebagai teknik dasar dan teknik lanjutan berupa teknik baca markah. Hasil penelitian menunjukkan bahwa bentuk preposisi yang ditemukan adalah preposisi  bentuk dasar dan   bentuk turunan berupa preposisi gabungan.  Jenis makna yang ditemukan adalah tempat berada, tempat asal, tempat tujuan, tempat tertentu; perbandingan, dan kesertaan.